The research history by an academician B. Dombrovskiy nervous system of vertebrates - Pichkur, T. V. (History of science and technology, 2013)
In the article research history is illuminated by an academician B.А. Dombrovskim nervous system of vertebrates. The detailed research provided research workers the scientist of trophism of animal by complete and reliable data on many general questions of morphology and gave explaining to the functional aspects of separate structures of organism